Hubungan Pengetahuan Produk dan Gaya Hidup Sehat dengan Minat Beli Minyak Sacha Inchi di Kota Bandung - Fuadiyah, Alda; Deliana, Yosini (Universitas Galuh, 2025)
Sacha inchi oil is a new product derived from the sacha inchi plant. Despite its numerous benefits, its sales in Indonesia remain low. This study aims to analyze the relationship between product knowledge and a healthy lifestyle on purchase interest in sacha inchi oil in Bandung City. The research method used is a survey by distributing online questionnaires to respondents who meet the criteria and reside in Bandung City. The data were analyzed descriptively and using Spearman's rank correlation to examine the relationship between product knowledge and a healthy lifestyle on purchase interest in sacha inchi oil. The results show a relationship between product knowledge and purchase interest in sacha inchi oil with a correlation coefficient of 0.528, indicating a strong relationship. Additionally, there is a relationship between a healthy lifestyle and purchase interest in sacha inchi oil with a correlation coefficient of 0.319, indicating a moderate or fairly strong relationship.